Histomorphological spectrum of ovarian tumors - A tertiary care center experience - Sampurna, K; Jyothi, B (Asian Journal of Medical Sciences, 2022)
Background: Ovarian tumors are a heterogeneous group of neoplasms with variable clinical, morphological, and histological features. Ovarian cancer is the leading cause of death in females. Aims and Objectives: (1) To study and characterize the ovarian tumors based on gross and histopathological features. (2) To study prevalence and age distribution of various ovarian tumors. (3) To study the clinical features in patients with ovarian tumors. (4)To compare the frequency of benign and malignant neoplasms of the ovary with other studies. Materials and Methods: This is a prospective study conducted in Upgraded Department of Pathology, Modern Government maternity hospital, and Osmania General Hospital, Hyderabad, Telangana from March 2018 to February 2021. A total of 200 ovarian tumors were studied. Results: Out of 200 ovarian tumors, 132 were benign, seven were borderline and 61 were malignant. The surface epithelial tumors were the most common tumors accounting for 159cases (79.5%), germ cell tumors were seen in 27 cases (13.5%), sex-cord stromal tumors formed 10 cases (5%), and metastasis in 4 cases (2%). Conclusion: Ovary is a common site of tumors in the female genital tract and usually presents with a variety of clinocomorphological and histological features. Benign are the most common, of these surface epithelial tumors are the commonest, affects mainly reproductive age group.